F62 Identification and verification of novel variables in quantitative motor tests (Q-motor) in huntington's disease, using the track-hd data set. (September 2018) - Pracht, Philip; Schubert, Robin; Barallon, Pascal; Habbel, Benjamin; Mittmann, Karin; Reilmann, Ralf
Abstract : Background: Clinical rating scales in clinical trials for Huntington's disease (HD) have shown limited sensitivity in the premanifest stage of HD and often suffer from inter- and intra-rater variability and bias. Thus, there is an unmet need for objective and reliable assessments to serve as outcome measures in clinical trials. The Q-Motor, a sensor-based assessment battery, was developed to provide accurate and precise quantification of motor performance. During the analysis of the TRACK-HD study, a couple of variables turned out to be particularly sensitive, but further approaches on testing alternative variables have not been conducted, yet. Objective: To identify novel conceptual variables for the Q-Motor digitomotography (speeded tapping) assessment, that have the potential to be more sensitive and robust particularly in the premanifest stage. The applicability of these variables should be investigated for cross-sectional and longitudinal analyses, using the TRACK-HD data. Methods: Q-Motor raw-data from the TRACK-HD study was used to extract the novel variables. The data sample included 4 year follow up data from 288 participants (age: 48 ± 10 years, female: 124, number of unaffected controls: 94). Statistical analyses were conducted using R. Generalized linear mixed models and ANOVA was used for group comparisons cross-sectional and longitudinally. Correlation with clinical rating scales and imaging parameters was performed. Results: Most novel identified variables allow discrimination between controls pre-HD and manifest HD groups. Some even show significance in the more subtle distinction between pre-HD subgroups. Most variables also show good correlations with the clinical Total Motor Score (TMS) and with several magnet resonance (MR) imaging variables. Conclusion: The sensitivity observed in the novel variables is comparable to that of previously used variables. However, the additional information may be useful for the creation of a combined measure, which will be explored in a next step.